The VANDELS survey: a strong correlation between Ly α equivalent width and stellar metallicity at 3 ≤ z ≤ 5. Issue 1 (9th May 2020) - Cullen, F; McLure, R J; Dunlop, J S; Carnall, A C; McLeod, D J; Shapley, A E; Amorín, R; Bolzonella, M; Castellano, M; Cimatti, A; Cirasuolo, M; Cucciati, O; et al.
ABSTRACT: We present the results of a new study investigating the relationship between observed Ly α equivalent width ( W λ (Ly α)) and the metallicity of the ionizing stellar population ( Z ⋆ ) for a sample of 768 star-forming galaxies at 3 ≤ z ≤ 5 drawn from the VANDELS survey. Dividing our sample into quartiles of rest-frame W λ (Ly α) across the range -58 A W λ (Ly α) 110 A, we determine Z ⋆ from full spectral fitting of composite far-ultraviolet spectra and find a clear anticorrelation between W λ (Ly α) and Z ⋆ . Our results indicate that Z ⋆ decreases by a factor ≳ 3 between the lowest W λ (Ly α) quartile (〈 W λ (Ly α)=-18 A ) and the highest W λ (Ly α) quartile (〈 W λ (Ly α)=24 A ). Similarly, galaxies typically defined as Lyman alpha emitters (LAEs; W λ (Ly α) 20 A ) are, on average, metal poor with respect to the non-LAE galaxy population ( W λ (Ly α) 20 A ) with Z ⋆ non-LAE ≳ 2 × Z ⋆ LAE . Finally, based on the best-fitting stellar models, we estimate that the increasing strength of the stellar ionizing spectrum towards lower Z ⋆ is responsible for 15-25 per cent of the observed variation in W λ (Ly α) across our sample, with the remaining contribution (75-85 per cent ) being due to a decrease in the H i /dust covering fractions in low- Z ⋆ galaxies.